Pengaruh Faktor Ekonomi Makro, Kestabilan Politik dan Harga Minyak Dunia pada Nilai Tukar Rupiah terhadap Dolar Amerika Serikat - Karimah, Zulfiniar Nur; Laulita, Nasar Buntu (Jurnal Maksipreneur, 2023)
The exchange rate value of the rupiah against the US dollar fluctuates and tends to depreciate throughout the year. So it is very important to analyze the factors that influence the exchange rates to maintain its stability. The relationship between several macroeconomic factors such as inflation, interest rates, GDP, and trade openness as well as political stability factors and world oil prices on exchange rates are the main topics of discussion in this study. Monthly data in time series 2010-2020, processed using the Eviews 12 and tested using the multiple linear regression method. There is a significant positive effect between interest rates, GDP, and world oil prices for the type of WTI on the exchange rates. Meanwhile, trade openness, political stability, and world oil prices for the Brent type have a significant negative effect on the exchange rates. As for the inflation variable, it does not have a significant effect on the exchange rates. The government as a policy maker is expected to be able to regulate macroeconomic factors, maintain political stability, and control the supply of crude oil properly to maintain the exchange rate stability.